Sustainability of Water Quality Monitoring System Through Riverbank Based Internet of Things - Abdul Rahim, Nur Fazrina; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2023)
Water is an essential resource for humans, ecology, health, and survival. Increased development near rivers has a negative impact on water quality, making it more difficult to provide a clean water supply. Furthermore, water pollution has resulted in a shortage of fresh water for use by consumers in their daily activities. This is taken seriously when in the absence of early detection, long-term cleaning is required to control the spread of water pollution. Water consumption contains harmful amounts of pollutants, which can pose health problems to water users and aquatic life. Therefore, in this project, a water quality monitoring system is developed to identify existing issues and issues that will arise. The implementation of IoT enables faster water quality monitoring and response times from the relevant authorities, thus enhancing the optimal warning system. The system functionality is when contamination is detected from the threshold change on the sensors data, Arduino will signal the Blynk application to send a warning notification to alert the authorities. The system correctly determined the status of the lake water by measuring a parameter that detects when tested. Experiments carried out throughout the study discovered that the proposed system has a high chance that the water quality could be in bad condition due to the case study and weather.